2012
DOI: 10.1111/j.1741-4520.2011.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirenomelia with a de novo balanced translocation 46,X,t(X;16)(p11.23;p12.3)

Abstract: We report a female fetus with sirenomelia with 46,X,t(X;16)(p11.23;p12.3) de novo. Fluorescence in situ hybridization (FISH) with bacterial artificial chromosomes were employed for narrowing down the breakpoint regions. On chromosome 16, the breakpoint was mapped in the region of RP11-453F10 (19 920 640-20 118 153 bp from 16pter). On chromosome X, the breakpoint was mapped in the region of RP11-794A15 (47 333 744-47 524 066 bp from Xpter). This is the first case report of sirenomelia associated with translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Very few chromosomal conditions have been reported in human cases of sirenomelia. Kurosawa et al () found a de novo balanced 46,X,t(X;16)(p11.23;p12.3) translocation. Gabriele and Gianpaola () described a triploidy mosaic sirenomelic fetus (69,XXX/46,XX) after karyotyping the chorionic villi.…”
Section: Sirenomelia In Chromosomal and Monogenetic Conditionsmentioning
confidence: 99%
“…Very few chromosomal conditions have been reported in human cases of sirenomelia. Kurosawa et al () found a de novo balanced 46,X,t(X;16)(p11.23;p12.3) translocation. Gabriele and Gianpaola () described a triploidy mosaic sirenomelic fetus (69,XXX/46,XX) after karyotyping the chorionic villi.…”
Section: Sirenomelia In Chromosomal and Monogenetic Conditionsmentioning
confidence: 99%
“…Cytogenetic studies in sirenomelia cases did not show any numerical or structural chromosomal abnormalities, with the exception of a reported case with a de novo X; autosome translocation t(X;16) (p11.23;p12.3) (Kurosawa et al, ). These authors could not assign any candidate gene related to blastogenesis in the region of the breakpoints.…”
Section: Discussionmentioning
confidence: 95%
“…Slides were analyzed using a completely motorized epifluorescence microscope (Leica DMRXA2) equipped with a CCD camera. Both the camera and the microscope were controlled using Leica CW4000 M‐FISH software (Leica Microsystems Imaging Solutions, Cambridge, UK) [Kurosawa et al, ].…”
Section: Methodsmentioning
confidence: 99%